Lutein and zeaxanthin - radio- and chemoprotective properties. Mechanism and possible use - Jakub Fiedorowicz; Małgorzata M. Dobrzyńska (National Institute of Public Health - National Institute of Hygiene, 2023)
Lutein and zeaxanthin are naturally occurring xanthophylls, mainly present in green, leafy vegetables and egg's yolk. Their presence is connected with blue spectrum light absorbance, including UV. This property, and fact, that these xanthophylls are accumulated by human eye's macula, leads to eye's protective functions of them including protection from age-related macular degeneration (AMD). Also, antioxidative features of lutein and zeaxanthin are boosting overall health of human body. Numerous studies proves anti-inflammatory and protective attributes of these compounds, based on many, different mechanisms. One of them is regulating redox potential in cells, and impact on expression of linked genes. In preventing of eye diseases, an important gene that is regulated by lutein and zeaxanthin is the Nrf2 gene, whose increased activity leads to optimizing the cellular response to reactive oxygen species (ROS) and preventing related diseases. Other research confirms antiproliferative properties of mentioned compounds in case of certain human cancer cell lines. There are e.g.: HepG2 (hepatitis cancer), MCF-7 (breast cancer), which treated in vitro with lutein solution showed reduction of cell growth. Lutein alone, during in vivo studies conducted on mice, exhibited also radioprotective properties, positively affecting the vitality of animals. Lutein provides also increasing of tolerance to UV radiation, reducing inflammatory processes in the skin and preventing oncogenesis. Low intake of lutein and zeaxanthin, associated with "western diet", rich in simple carbohydrates and processed food, common in developed countries, including Poland, is linked with diabetes and obesity incidence. Assuming, lutein and zeaxanthin significantly affect the well-being of the human body, and their appropriate amount in diet can help reduce risk of many diseases. For supplementation, the optimized dosage of these xanthophylls includes doses of 10 mg for lutein and 2 mg for zeaxanthin, and it is recommended to consume along with fats or meals rich in fats.